194k views
2 votes
How to solve −3d + 10 = 43

User Metiu
by
5.3k points

2 Answers

4 votes

Answer:

-3d = 43-10

-3d = 33

d = 33/-3

d = -11

6 votes

Answer:

d = 11

Explanation:

Simplifying

3d + 10 = 43

Reorder the terms:

10 + 3d = 43

Solving

10 + 3d = 43

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-10' to each side of the equation.

10 + -10 + 3d = 43 + -10

Combine like terms: 10 + -10 = 0

0 + 3d = 43 + -10

3d = 43 + -10

Combine like terms: 43 + -10 = 33

3d = 33

Divide each side by '3'.

d = 11

Simplifying

d = 11

Hope this helps!

User Nabn
by
5.2k points